في سند الحديث النبوي عند بعض المستشرقين (Common Link) شبهة وضع الحديث عن طريق الراوي المركزي: (دراسة تحليلية نقدية) - Anwar, Saepul; Kusnadi (Jurnal Indragiri Penelitian Multidisiplin, 2024)
This research delves into studying the suspicion of Hadith fabrication through the concept of the "central narrator" in the chain of narration according to some orientalists who attempt to cast doubt on the authenticity of Prophetic Hadiths from the Messenger of Allah, peace be upon him, through an analytical and critical approach. The objectives of this research are firstly: to understand the true essence of the theory of the central narrator as perceived by some orientalists before critiquing it. Secondly: to comprehend the methodology adopted by some orientalists in presenting this theory in the chains of Hadith narrations. Thirdly: to critique and invalidate this theory in an attempt to uphold the authenticity of Prophetic Hadiths as the secondary source for understanding religious rulings and teachings. The hypotheses of this research are: The first hypothesis suggests that the theory posits that most of the currently recorded Prophetic Hadiths, in terms of their chains of transmission, are centered around narrators in the layer after the major successors of the companions, whom these narrators are referred to as the central narrators or what is known in English as the "common link". Based on this premise, some orientalists believe that the majority of Prophetic Hadiths are fabricated by these central narrators. The second hypothesis suggests that the methodology adopted by some orientalists in presenting this theory involves analyzing the chain of transmission through the following steps: first, identifying the text of the Hadith intended for analysis; second, tracing the text of the Hadith in Hadith books; third, gathering the chains of transmission for that Hadith; and fourth, constructing that chain of transmission into a unified entity. The third hypothesis suggests that the theory of the common link or the central narrator in the chain of Hadith transmission is invalidated by the theory of evidence and corroborations in Prophetic Hadiths, which focus on the two fundamental components of Hadith: the chain of transmission and the text.